Kajian Empiris Motivasi Berprestasi dan Disiplin Kerja terhadap Kinerja Dosen: Perceived Organizational Support sebagai Pemoderasi - Khadijah, Della Zhafira; Mas, Nasharuddin; Survival, Survival (Jurnal Ilmiah Wahana Pendidikan, 2023)
The research objective was to obtain empirical evidence of the role of perceived organizational support in moderating the effect of achievement motivation and work discipline on lecturer performance. The population in this study were all lecturers at Tribhuwana Tunggadewi University, totaling 191 people. The number of samples is determined by the slovin formula which produces 99 lecturers as respondents. The sampling uses probability sampling with the type of proportionate stratified random sampling. The analysis technique uses variance-based SEM (Structural Equation Model), namely PLS (Partial Least Square) with the help of the SmartPLS program. The results of the study show that achievement motivation can improve lecturer performance. Work discipline has not been able to improve lecturer performance. Perceived organizational support succeeded in strengthening the effect of achievement motivation on lecturer performance. Perceived organizational support succeeded in strengthening the effect of work discipline on lecturer performance.